Implementasi Earning Management Pada Lembaga Keuangan Dengan Prinsip Akuntansi Syariah - Fitriani Fitriani; Ersi Sisdianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Companies such as financial institutions in carrying out operational activities always want to obtain high profits such as profit engineering. Earnings engineering is one of the contemporary issues in finance, especially in Indonesia. In several reports in a large company there are 77% of senior managers involved in unethical behavior by carrying out scandals that are motivated by earnings management. This is problematic for the development of accounting, especially sharia accounting. Study aims to analyze the implementation of Islamic earnings management in Islamic accounting. In this study teh method use is the literatur review by collecting secondary data from various related journal. The results show that there are still earnings engineering practices in companies and financial institutions in Indonesia. For this reason, sharia principles really need to be emphasized in order to improve the quality of sharia accounting that is completely free from fraudulent practices. One of the appropriate efforts is to apply sharia accounting in conducting profit-sharing financing, proper and effective monitoring must be carried out with adequate supervision and reporting, so that companies such as Islamic banks or companies can avoid earning management and profit engineering. Financial institutions that apply sharia accounting principles are required to implement Islamic earnings management as a profit management practice in accordance with Islamic religious rules and ethics.